ENHANCING COOPERATION SKILLS OF GROUP B CHILDREN THROUGH ROLE-PLAYING GAMES IN EARLY CHILDHOOD EDUCATION - Tiara Kapiso; Lukman Arsyad; Munirah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2026)
Cooperation is an essential aspect of early childhood social-emotional development. Initial observations of Group B children at an early childhood education institution indicated that children’s cooperative ability was still low, particularly in interacting with peers, sharing roles, helping others, and following group activity rules. This study aimed to improve children’s cooperative ability through role-playing games. The research employed Classroom Action Research based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 14 Group B children, consisting of 6 boys and 8 girls. Data were collected through observation and documentation and analyzed using descriptive quantitative analysis by calculating the percentage of children’s developmental achievement. The findings showed an improvement in the average score from 28.57% in the pre-cycle to 69% in Cycle I and 96% in Cycle II. By the end of Cycle II, all children reached the Very Well Developed category. These findings indicate that role-playing games are effective in improving children’s cooperation because they provide opportunities for children to interact, share roles, help each other, communicate, and follow rules in an enjoyable learning atmosphere. The implication of this study is that role-playing games can be used as an alternative learning strategy for early childhood teachers to strengthen children’s social-emotional development, particularly cooperation skills, through meaningful, active, and child-centered learning experiences.